Gemengde scholen als hefboom voor succes? - Emmanuelle Lenel (Brussels Studies)
This article examines the democratic ideal of diversity in the broad sense, in the field of education. Based on two case studies of schools in Brussels which meet the challenges of diversity in Brussels in two very different ways, the author uses ethnographic data to put universalist and communitarianist integration models into perspective. She attempts to show that these two types of school do not simply constitute an ethical and philosophical alternative, but that they contribute to shaping different students. Beyond their impact on educational success and segregation, each model of school favours the three logics differently – strategies for success, integration and personal growth – which students must combine within the school environment.